Peningkatan Kesadaran Masyarakat Terhadap Lingkungan Melalui Penyuluhan Pupuk Organik di desa Sumberbulus, kecamatan Ledokombo-Jember - Ade Nisa’ Kartika Azzahra; Dwiki Yudistira; Ikfira Agustina Putri; Reno Kurnia Ramadhan; Rosita Dina Dwi Ayunliana; Fathor Rosi; Frida Oktavia Putri Hermanto; Reza Zarkasih Adytia; Ridho Anil Shohibul Falah; Haikal Alhamdi Sirojul Alam; Mohammad Rofik Usman (Universitas Mathla'ul Anwar Banten, 2022)
INCREASING PUBLIC AWARENESS OF THE ENVIRONMENT THROUGH ORGANIC FERTILIZER COUNSELING İN SUMBERBULUS VİLLAGE, DİSTRİCT OF LEDOKOMBO-JEMBER. Sumberbulus Village is a village where most of the residents work as farmers. The farmers in this village are very dependent on the results of their agricultural production on inorganic fertilizers, because it can speed up the harvest period. But the continuous use of inorganic fertilizers can pollute the environment. The counseling was carried out at the Sumberbulus Village Hall, district of Ledokombo-Jember Regency on August 9, 2022. The implementation of this activity was with the lecture method accompanied by questions and answers and the practice of making organic fertilizer. Participants consisted of 50 farmers in Sumberbulus Village. Organic fertilizer is an environmentally friendly technology. How to make organic fertilizer using materials that are quite easy to find and household waste. This activity has an impact in increasing the insight and understanding of farmers regarding sustainable agricultural management so that the resulting agricultural production has a long-term effect, and is safe for the environment.